The small business online marketing handbook : - Tsai, Annie (Wiley, 2013)
The small business marketing experts at Demandforce help owners kick off their online strategy. Small business owners are exceptional at delivering on their product or service. Many, however, don't know where to start when it comes to online marketing. The Small Business Online Marketing Handbook will show you how to effectively leverage email, social, online, and network marketing to get new customers and keep existing customers coming back. Author Annie Tsai shows you how to refocus just a small percentage of an offline marketing budget and create exponential return for your business. Author Annie Tsai is a popular blogger and Chief Customer Officer for Demandforce, an automated Internet marketing and communication company specializing in small- to medium-sized businesses, recently acquired by Intuit Features spot interviews and "do this now" advice from resident experts at Demandforce, including the founders With the proliferation of social media and the consumer voice on the web, small business owners need to take a deliberate approach to leveraging this new marketing channel to effectively convert online conversations into offline sales. The Small Business Online Marketing Handbook shows you how